Renewable Energy - Kaltschmitt, Martin (Springer, 2012)
This book presents the physical and technical principles of promising ways of utilising renewable energies. In this context, firstly the main characteristics of the available renewable energy streams are outlined. Subsequently, the book presents the technologies of heat provision from passive and active solar systems, ambient air, shallow geothermal energy as well as energy from deep geothermal sources. In the preceding chapters the book addresses the processes of electricity generation from solar radiation (photovoltaic and solar thermal power plant technologies), wind energy, and hydropower. In addition, a brief discussions of harnessing ocean energies is included.